LEARNER AUTONOMY ON ESSAY WRITING ACCURACY - Moh. Hafidz (Jurnal Pendidikan Edutama, 2018)
Abstract: Learner autonomy on writing is independently teaching and learning that keeps students’ control to explore their knowledge and experiences in written language, find out and evaluate their errors based on the conceptual courses to make accurately simple essay. The aim was to know the effectiveness of the learner autonomy on writing accuracy. This quantitative research conducted in one group pretest and posttest design. The number of samples was 21 students in Bangkalan. The instrument were tests to gain students’ writing score before and after treatment. Researcher statistically analyzed the data using SPSS 23 version by running a Paired Samples Test. The result shown the means of pretes score was 66,83 and posttest score was 74,57, Paired Samples Correlations was 0,614 (strong correlation). Significance was 0,005, it means that  a (0,05) is higher than r value (0,005) with high variance of mean value (14,091). As a result, the hypothesis (H1) was received that learner autonomy contributed effectively to learners’ in organizing own ideas (Ene, 2006) such as making a topic  map becomes some explanable sub-topics, writing down main and supporting idea, clustering some objects, editing next and learners  absolutely accumulate some selected vocabularies inappropriate topics  (Chengping W, 2008).Keyword: Learner Autonomy, Learning process, outcomesAbsrak: Pembelajaran otonomi  adalah pembelajaran mandiri yang mengontrol mahasiswa untuk menyampaikan gagasan dan pengalamannya, mencatat dan mengevaluasi kesalahan yang terjadi dalam penulisan esai sederhana berdasarkan pembelajaran yang tersetruktur. Tujuan adalah untuk mengetahui efektifitas pembelajaran otonomi terhadap akurasi tulisan secara statistik. Penelitian ini dilakukan dengan menggunakan desain tes awal dan akhir. Jumlah sampel terdiri dari 21 siswa di Bangkalan. Isntrumen yang digunakan adalah tes untuk mengetahui hasil nilai mahasiswa sebelum dan sesudah melakukan pembelajaran otonomi. Peneliti menganalisa data dengan menggunakan versi SPSS 23 dengan menggunakan sampel tes  yang berpasangan. Hasil rata-rata tes awal adalah 66,83 dan tes akhir adalah 74,57, dengan corelasi sampel berpasangannya adalah 0,614 (kuat). Sedangkan signifikansinya adalah 0,005, artinya a (0,05) lebih besar daripada r value (0,005) dengan varian nilai rata-rata yang tinggi (14,091). Hasil hipotesis (H1)-nya diterima bahwa pembelajara otonomi berkontribusi secara efektif terhadap pengorganisasian gagasan mahasiswa sendiri (Ene, 2006) seperti memetakan suatu topik menjadi sub-topik yang mudah dijelaskan, pengelompokan objek tertentu untuk dijadikan topik, kemudian mengeditnya dan tentunya dapat memilih kosakat-kosakata yang sesuai dengan topiknya  (Chengping W, 2008).Kata Kunci: pemanfaatan media, pembelajaran sains